Mechanical properties of hybrid vetiver/banana fiber mat reinforced vinyl ester composites. Issue 4 (June 2022) - Stalin, A; Mothilal, S; Vignesh, V; Sanjay, MR; Siengchin, Suchart
Green sustainable life and biofibers play a vital role in achieving eco-friendly environment and great opportunities for fabricating the products. This work focused on the effect of the hybrid mat as reinforcement in vetiver/banana fiber mat reinforced vinyl ester composites. Composites plates were fabricated at 45° and 90° directions in ten different combinations by the compression molding machine. The mechanical properties of composites plates were tested as per ASTM standard. The morphological behaviour of tested specimens were evaluated by SEM. The hybrid double-layer fiber mat composites in longitudinal direction exhibit optimum results in tensile and flexural properties. However, it is found that vetiver double-layer fiber mat composites at 90° direction, indicating better impact strength than a banana and hybrid fiber mat composites. SEM images provided that composite properties are dependent on interface bonding between the fibers and matrix.